India of my dreams/ edited by Surendra Kumar and Pradeep K.Kapur - Surendra Kumar (ed.) (New Delhi, 2008)
A unique collection of thoughts, ideas, views and vision of some of the brightest brains and most respected individuals-from senior cabinet ministers to role model captains of industry; from internationally acclaimed economists to diplomats par excellence and think-tank honchos; from IT innovators to provocative journalists-all jostle together in this volume sharing glimpses of India of their dreams.
Keywords: Economic forcasting - India